Towards a Legal and Regulatory Framework for South African Domestic Remittances: Some Considerations - Lawack, Vivienne (African Human Mobility Review, 2021)
This paper is an exploratory study that examines the legal and regulatory frameworkfor domestic remittances within the South African legal context. The author makessome proposals for consideration in the review of the National Payment SystemAct No 78 of 1998 (NPS Act) with regards to domestic remittances as a retail, lowvaluepayment service. To this end, the paper provides an understanding of domesticremittances, the transaction, process and channels used. It also contextualizesdomestic remittances within the South African National Payment System (NPS) andfinally examines the current gaps that can be remedied through the review of the NPSAct. The author argues that if financial inclusion is to be promoted, the regulatoryframework pertaining to domestic remittances should enable, rather than inhibit theuse of domestic remittances as a payment service.